446 Impacts of Ergot Alkaloid Exposure During Mid and Late Gestation on Wether Performance and Glucose, Insulin, and NEFA Values. (7th December 2018) - Greene, M; Britt, J; Miller, M; Adams, S; Duckett, S
Abstract: The objective of this study was to evaluate the effects of feeding ergot alkaloids from endophyte-infected tall fescue seed to gravid ewes during two stages of gestation on male offspring performance. Suffolk ewes (n=60; 83kg) estimated to be carrying twins at d35 of gestation were stratified by genotype (AA, AG, GG; DRD2 SNP) to endophyte-free tall fescue seed (E-) or endophyte-infected tall fescue seed (E+; 4.14µg ergovaline+ ergovalinine/g) during two stages of gestation (MID: d35–d85 and LATE: d86–parturition) in a 3 x 2 x 2 factorial. Wethers (n=44) were finished to 59 kg or d185 post weaning. Blood samples were collected at birth, weaning, end of the growing period, and end of the finishing period. A subsample of wethers from ewes that gave birth to twins from E-/E- and E+/E+ ewes were selected for glucose, insulin, and NEFA analysis. Glucose, insulin, and NEFA values were not different by treatment ( P >0.05). Lamb birth weight was lower ( P< 0.05) for E-/E+ and E+/E+ ewes. Weaning weight for all lambs was lower for E+/E+ lambs. Significant interaction was found between maternal genotype and treatment for weaning average daily gain for all lambs ( P< 0.05), with GG:E+/E+ gaining less. Additionally, GG:E-/E+ reticulum ( P< 0.05), rumen ( P< 0.05), and large intestine ( P< 0.01) were heaviest and total days to harvest ( P< 0.01) was the shortest. Interactions between maternal genotype and treatment tended to be different for feed efficiency during the growing phase ( P< 0.06) and total feed efficiency ( P< 0.10). GG:E-/E+ had improved growing phase efficiency and AA:E-/E+ had lower total feed efficiency. Small intestine weight tended ( P 0.10) to be different by treatment, E-/E+ had higher values. Lambs born to ewes with different DRD2 genotypes that were exposed to endophyte-infected tall fescue during MID and LATE gestation have altered postnatal growth.